Suplementasi Zinc Mempercepat Masa Penyembuhan dan Pencegahan ISPA pada Anak Usia 2-5 Tahun - Sukmawati Sukmawati; Ahmad Ahmad; Luluk Widarti (FORIKES, 2020)
Upper respiratory tract infection or ARI is an acute infection that attacks one component of the upper respiratory tract. West Nusa Tenggara Province has the highest incidence of ARI. In 2016 there were 16,085 cases of ARI in children under five, and in Bima Regency there were 1,429 cases of ARI cases in Bima, which were 1,429 cases in 2016. The benefits of zinc for human health are enormous, this mineral is very helpful for various body functions to run normally. This study was to determine the effect of zinc supplementation on the healing period of ARI and its prevention in children aged 2-5 years in the Work Area of the Madapangga Community Health Center, Madapangga District, Bima Regency in 2018. This type of research was analytical survey research, the design of this study was Quasi-experimental model